Polskie dylematy w „czasach aniołów”. Próby budowania bezpieczeństwa zbiorowego w Europie w latach 1926-1929 a koncepcje polskiej polityki zagranicznej w świetle „Gazety Warszawskiej” - Węclewska, Marta (Acta Universitatis Lodziensis. Folia Historica, 2008)
One of the most difficult tasks regarding Polish foreign policy throughout the intewar period was developing its international position. A position which would be compatible with the Polish “raison d’etat” of the time; the attempt to forge on international agreement of European security. This problem, among other things, was based on the relationship between Poland and Germany and, as a consequence, Polish policy was aimed at sticking to the Treaty of Versailles or obtaining a on their part similar guarantee in case this Treaty was to be abolished. The Germans, on their part, still wished to dismantle, what they belived to be punitive dictate, laid out at Versailles. They realised, however, that they, under the representation of Gustav Stresemann, the German Foreign Minister, had to change theit tactic into more peaceful ones. It was well known that, the Germans overtly harboured designs on the Polish territories of Silesia, the Pommerania and Prusia corridor and Danzig, a free city, whose foreign affairs were determined by Poland. Under such circumstances the most important task of Polish foreign policy relied upon defending the best position it could in European affairs and keeping the diplomatic initiative. Nevertheless, that said, this task was incompatible with the main trends of European diplomacy. The policy of friendship between western countries, especially Germany, France and Great Britain had led to the inclusion of Germany into the Council of the League of Nations, dissolving the Inter-Allied Commision of Control and finally the evacuation of the Rhineland. In all these matters Poland had a little or no to say. Her position being limited to that of a witness. Obviously the weakening international position of Poland was well observed and described by the “The Warsaw Gazette” - the then a Polish nationalists’ newspaper. The deadlock between the Polish foreign policy objectives and that of the European diplomatic trends could not be rectified. Even the National Democratic Party, who was at the time in opposition and thus having less responsibility for policy had no clear idea on how to find a solution. Journalists working for “The Warsaw Gazette” on the one hand correctly recognised the direction of the political changes in Europe, favouring Germany, but on the other, did not accept, some would say illogically, that these changes would result in a loosening of the alliance with France. Due to Poland's constant efforts in defending the system set out in the Treaty of Versailles, its influence on the great international conferences was marginalized. Disappointed by that fact "Gazette" journalists pressed on the importance of the French alliance as a valuable and safeguard of the security of Poland, even if the policy of friendship with Germany, made by the French government, was not, from Polish point of view, fair. This was done as it was still believed that Warsaw and Paris had common agendas on foreign affairs, especially when it came to maintaining the post-war European system. However, as pessimism reached its zenith, commentators from “The Warsaw Gazette” suggested all nation's forces be concentrated to the defence of the country and, as far as they were concerned, Poland needed help from western allies. These fundamental difficulties in Polish dilemmas were never solved. Even today the question still remains whether this tragic finals was the fault of the Polish foreign policy or independent factors connected with the contemporary international trends.